Chronic lymphocytic leukemia cells with allelic deletions at 13q14 commonly have one intact RB1 gene: evidence for a role of an adjacent locus. - Liu, Y (1993)
We have previously shown that 30% of patients with B-cell chronic lymphocytic leukemia (B-CLL) have hemizygous deletions of the retinoblastoma (RB1) gene at 13q14. RB1 gene deletions may thus participate in malignant transformation of B-CLL, but it is also possible that a neighboring gene on 13q is the relevant one. To answer this question the remaining RB1 allele of eight clones with hemizygous deletions was studied by reverse transcription-polymerase chain reaction (RT-PCR), single-strand conformation polymorphism (SSCP) analysis, and immunofluorescense techniques. Cells from 10 patients without RB1 gene deletions were also studied by these methods. Lack of RB1 mRNA and RB protein expression was seen in leukemia cells from one of the patients. All other cases were found to be normal with regard to immunofluorescense, RT-PCR, and SSCP analysis, indicating at least one functional RB1 allele and supporting the importance of another gene in the 13q14 deletions. We then performed extended Southern blot analyses of the 13q region, using probes for 10 different loci. In 14 of 31 CLL clones (45%), deletions of a region telomeric to the RB1 gene (D13S25) were observed. In 4 of the cases the deletions were homozygous. Hemizygous deletions of the RB1 gene were observed in 11 of these patients and in none of the patients without D13S25 deletions. These data thus indicate that a gene(s) telomeric to RB1 is involved in the malignant transformation of CLL clones and that deletions of this region are a common event in this disease.